Applications of Nanomaterials in Biomedical Imaging and Cancer Therapy (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This reprint, part of the Biology and Medicines section of Nanomaterials, presents a curated collection of peer-reviewed articles from the successful third edition of our Special Issue. Building on the achievements of previous editions, this volume highlights cutting-edge research on the design and application of nanomaterials for biomedical imaging and cancer therapy. The included works explore innovative strategies such as targeted drug delivery, photothermal and photodynamic therapy, theranostic platforms, and advanced imaging agents. Topics range from experimental studies at the cellular, preclinical, and clinical levels to computational modeling of nanomaterial–biological interactions. Together, these contributions demonstrate how nanotechnology is transforming precision oncology and diagnostic imaging. This reprint serves as a valuable resource for researchers, clinicians, and industry professionals seeking the latest developments in nanomedicine and cancer treatment.